Everyday Heroism: Maintaining Organizational Cultures of Wellness and Inclusive Excellence Amid Simultaneous Pandemics. (22nd December 2020) - Fassiotto, Magali; Valantine, Hannah; Shanafelt, Tait; Maldonado, Yvonne
Abstract : Health care professionals and the institutions in which they work are being stretched to their limits amidst the current COVID-19 pandemic. At the same time, a second longstanding pandemic has been brought to the fore: the entrenched system of racial injustice and oppression. The first pandemic is new, and to date, substantial resources have been allocated to urgently addressing its mitigation; the second has a long history with inconsistent attention and resources but has recently been spotlighted more intensely than at any time in the nation's recent past. The authors contend that these 2 simultaneous pandemics have brought forth the need for institutions in the United States to make a renewed commitment to respect, wellness, diversity, and inclusion. While investment and leadership in these domains have always been essential, these have largely been viewed as a "nice-to-have" option. The events of much of 2020 (most notably) have illustrated that committing to and investing in policies, programs, centers, and leadership to drive change in these domains are essential and a "need-to-have" measure. The authors outline the necessity of investing in the promotion of cultures of inclusive excellence at both individual and organizational levels to coordinate a united response to the simultaneous pandemics. It is in the interests of health care systems to consider the wellness of the workforce to overcome the longer-term economic, systemic, and social trauma that will likely occur for years to come at both the individual and institutional levels. Maintaining or augmenting investment is necessary despite the economic challenges the nation faces. Now is the time to cultivate resilience and wellness through a renewed commitment to cultures of respect, diversity, and inclusion. This commitment is urgently needed to support and sustain the health care workforce and maintain outstanding health care systems for future generations.